Underwater Investigation and Analysis of Upstream Face for a Built 40 years' and 6 km Long Embankment Dam in Africa. Issue 1 (August 2020) - Jinqiu, Liang; Jie, Tang; Yu, Tang; Ji, Lv
Abstract: The world's hydropower has experienced considerable development. With the coming of the post hydropower era, the business of new projects will gradually decrease, and meanwhile, the business of hydropower station renovation and dam maintenance will gradually increase. This paper introduces the methodology and the finding of the underwater investigation, analyses the upstream face stability and recommends solutions of rehabilitation for a built 40 years' and 6 km long embankment dam in Africa, aiming to provide a reference for similar projects of dam maintenance.